Bacterial Amyloid Formation: Structural Insights into Curli Biogensis. Issue 11 (November 2015) - Van Gerven, Nani; Klein, Roger D.; Hultgren, Scott J.; Remaut, Han
Abstract : Curli are functional amyloid fibers assembled by many Gram-negative bacteria as part of an extracellular matrix that encapsulates the bacteria within a biofilm. A multicomponent secretion system ensures the safe transport of the aggregation-prone curli subunits across the periplasm and outer membrane, and coordinates subunit self-assembly into surface-attached fibers. To avoid the build-up of potentially toxic intracellular protein aggregates, the timing and location of the interactions of the different curli proteins are of paramount importance. Here we review the structural and molecular biology of curli biogenesis, with a focus on the recent breakthroughs in our understanding of subunit chaperoning and secretion. The mechanistic insight into the curli assembly pathway will provide tools for new biotechnological applications and inform the design of targeted inhibitors of amyloid polymerization and biofilm formation. Trends: CsgC acts as a chaperone to prevent or neutralize premature, periplasmic amyloidosis of curli subunits. The protein does so at low substoichiometric ratios and in the absence of ATP. The CsgG lipoprotein forms a composite transmembrane β-barrel. Transition from a soluble prepore to the outer membrane-bound pore conformation entails nonamerization and extension of two adjacent β-hairpins per subunit. The CsgG nonamer forms a constitutive peptide diffusion channel that cooperates with CsgE to expel curli subunits in an entropy-driven process. CsgE forms a periplasmic, nonameric secretion adaptor that binds and caps a preconstriction chamber in the curli transporter CsgG. CsgF acts as a CsgG-bound curli assembly factor that coordinates the function of the curli nucleator CsgB with CsgG's secretion of the major curli subunit CsgA.